2012
DOI: 10.1111/j.1365-2133.2012.11113.x
|View full text |Cite
|
Sign up to set email alerts
|

An educational programme for patients with psoriasis and atopic dermatitis: a prospective randomized controlled trial

Abstract: Evaluating this form of educational programme, by means of a single-centre RCT, indicates its added value in the longer term management of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(156 citation statements)
references
References 16 publications
0
152
2
Order By: Relevance
“…Bostoen and colleagues evaluated a 12-week group-based education program for adults with AD and psoriasis [31]. The 12-week program consisted of 2-h sessions twice a week, including education on the skin disease, education on a healthy lifestyle, stress management techniques (exercise, yoga, mindfulness meditation), and medical feedback.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bostoen and colleagues evaluated a 12-week group-based education program for adults with AD and psoriasis [31]. The 12-week program consisted of 2-h sessions twice a week, including education on the skin disease, education on a healthy lifestyle, stress management techniques (exercise, yoga, mindfulness meditation), and medical feedback.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies included in this review suggested reduced economic burden and/or dermatological healthcare use for patients and families participating in multidisciplinary AD interventions, compared with standard medical treatment [27,32,33]. However, results were not consistent, with one study finding no differences in medication use or healthcare costs between the treatment and control groups [31]. More research is needed to better understand the cost-benefit analysis of providing multidisciplinary care for AD, given both high costs of treatment for severe AD, as well as the time and resource intensive nature of multidisciplinary treatments [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more aggressive approach with systemic agents or biologicals used earlier in the treatment paradigm with the goal of complete clearance may change the natural history of the disease, help more patients to achieve long-term remission, and improve long-term outcomes (26,27). One initiative to be explored further is the concept of multidimensional patient education, which was shown to improve patient outcome in a single-centre study (90).…”
Section: The Relationship Between Psoriasis and Other Imidsmentioning
confidence: 99%
“…In a recent parallel-group study from Belgium, the intervention group (n= 21) participated in a 12-week educational program (2 hours twice a week) given by a multidisciplinary team [29]. Despite a broad variety of issues being discussed with the patients during the lessons, no significant effects at 3 months were observable.…”
Section: Educational Training Programs For Adult Patientsmentioning
confidence: 99%